The method of reducing the intensity of magnetic field outside high voltage power substations - Shevchenko, S.; Okun, O.; Volokhin, V. (НТУ "ХПИ", 2013)
This work looks at theoretical methods for reducing the magnetic field generated outside the area of high voltage power substations. It has been shown that changing the construction of busbar wires is an effective measure that facilitates a reduction in the intensity of electromagnetic fields generated inside and outside the area of a substation. The measures connected with the phase sequence alternating of busbar wires can be implemented at the design stage and do not require an additional cost for implementation.

В данной работе рассматриваются теоретические методы уменьшения магнитного поля за пределами подстанций высокого напряжения. Было показано, что чередование фаз проводов соседних ошиновок влияет на снижение интенсивности магнитного поля за пределами подстанций высокого напряжения, и эти меры могут быть реализованы на стадии проектных работ, не требуя дополнительных затрат для их реализации.
Keywords: electromagnetic processes; impact on humans; environment; systems of protection; busbar; high voltage; phase sequence; процессы электромагнитные; системы защиты; шины электропитания; напряжение высокое; последовательность фаз